Aqueous Triple-Phase System in Microwell Array for Generating Uniform-Sized DNA Hydrogel Particles - Masukawa, Marcos Kunihiro; Okuda, Yukiko; Takinoue, Masahiro (Frontiers in Genetics, 2021)
DNA hydrogels are notable for their biocompatibility and ability to incorporate DNA information and computing properties into self-assembled micrometric structures. These hydrogels are assembled by the thermal gelation of DNA motifs, a process which requires a high salt concentration and yields polydisperse hydrogel particles, thereby limiting their application and physicochemical characterization. In this study, we demonstrate that single, uniform DNA hydrogel particles can form inside aqueous/aqueous two-phase systems (ATPSs) assembled in a microwell array. In this process, uniform dextran droplets are formed in a microwell array inside a microfluidic device. The dextran droplets, which contain DNA motifs, are isolated from each other by an immiscible PEG solution containing magnesium ions and spermine, which enables the DNA hydrogel to undergo gelation. Upon thermal annealing of the device, we observed the formation of an aqueous triple-phase system in which uniform DNA hydrogel particles (the innermost aqueous phase) resided at the interface of the aqueous two-phase system of dextran and PEG. We expect ATPS microdroplet arrays to be used to manufacture other hydrogel microparticles and DNA/dextran/PEG aqueous triple-phase systems to serve as a highly parallel model for artificial cells and membraneless organelles.